The Core Components and Instruments of the Therapeutic Relationship in Musculoskeletal Physiotherapy: A Systematic Integrative Review - Puustinen, Sini; Kvist, Tarja; Stolt, Minna (Wiley, 2026)
Background
The therapeutic relationship is meaningful and valuable to patients in rehabilitation and is positively associated with improved rehabilitation outcomes. Despite its central role, a comprehensive understanding of what constitutes the therapeutic relationship in physiotherapy and how it can be assessed is yet to be achieved.
Objective
This study aimed to identify the core components of the therapeutic relationship and the patient-reported instruments used to assess it in musculoskeletal physiotherapy.
Methods
A systematic integrative review was conducted. Six databases (CINAHL, PubMed/Medline, Scopus, Web of Science, The Cochrane Library, and PEDro) were searched. Two reviewers independently conducted study selection and methodological quality appraisal. Data were synthesised using inductive qualitative content analysis.
Results
Eighteen studies were included. Two core components and six subcomponents of the therapeutic relationship in musculoskeletal physiotherapy were identified: (1) therapeutic partnership (partnership and therapeutic communication) and (2) collaborative person-centred physiotherapy (collaboration; a holistic and individualised approach; coherent, competent, and credible physiotherapy; and empowerment support). Six instruments used to assess therapeutic relationships in musculoskeletal physiotherapy were identified.
Conclusions
In musculoskeletal physiotherapy, the therapeutic relationship is a multidimensional and dynamic construct encompassing therapeutic partnership and collaborative person-centred practice. Physiotherapists can actively influence the therapeutic relationship by utilising multimodal communication, implementing person-centred care strategies, and supporting patients' agency and empowerment. Existing patient-reported therapeutic relationship instruments capture these components only partially. Future research is needed to strengthen conceptual clarity and refine both the operationalisation and assessment of the therapeutic relationship in musculoskeletal physiotherapy.